Two Novel Decoding Algorithms for Turbo Codes Based on Taylor Series in 3GPP LTE System - Jian Wang; Jianping Li; Chaoshi Cai (Institute of Advanced Engineering and Science, 2014)
This paper proposes two novel methods to simply Logarithmic Maximum a posteriori (Log-MAP) algorithm for turbo codes in the Third Generation Partnership Project Long Term Evolution (3GPP LTE). Firstly, we exploit a new function to replace the logarithmic term in the Jacobian logarithmic function based on Taylor series, which has the best approximated accuracy compared with the existing methods. With this method, we get algorithm I. Secondly, to further simplify the complexity, we propose a new piece-wise ladder function to approximate the logarithmic term according to algorithm I. In this way, we obtain algorithm II. Simulation results show that the performance of the algorithm I is most close to the optimal algorithm. Algorithm II owns the complexity which is similar to the MAX-Log-MAP algorithm, meanwhile it can offer 0.37-0.4db performance gains than MAX-Log-MAP algorithm. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.2547